Investigation of effects of residual stress on the stiffness of MEMS devices - Law, Xin Ling. (2011)
In this thesis, an analysis was conducted to investigate the effects of residual stress on the stiffness of MEMS devices. Three case scenarios using a simple model are designed in order to make a comparison. By comparing the different scenarios, the displacement and frequency difference caused by the stress generated in a simplified model can be monitored.